Application of The Certainty Factor Method to Detect Android Based Rheumatoid Arthritis - Agus Iskandar (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
A system designed to assist in providing the final knowledge of rheumatoid arthritis that occurs. the expert system here imitates or is similar to an expert in knowing and detecting the initial symptoms of what is happening. This system was built using Android which can be installed by the user, this system helps in dealing with conditions that occur in rheumatoid arthritis. From the research conducted to produce an android-based expert system for the final diagnosis of conditions using the Certainty Factor method, it can provide information about 5 types of rheumatoid arthritis diagnoses, 10 symptom data, and provide information about causes to suggestions for final treatment. The results of testing using the Alpha Test on 15 participants were obtained to install the expert system first on mobile phones, the answer option